HQtrônicas e realidade aumentada (RA): novas potencialidades narrativas - PRADO, Jordana Inácio de Almeida (2012)
This master's research presented to the Pós-Graduation Program in Cultura Visual of FAV/UFG, in the research line Poéticas Visuais e Processos de Criação, is intended to study HQtrônicas an intermedia narrative - and the technology of Augmented Reality (AR), trying to show the narratives possibilities opened by this technology when it works with the language of HQtrônicas. Besides the investigations necessary for the theoretical and conceptual production, an experimental art work was developed, a practical exercise that incorporates the AR as a new possibility for the emerging language of HQtrônicas, showing other alternatives that were not experimented before in the HQtrônica´s structure.